P–T–time (phengite Ar closure) history of spatially close-outcropping HP and UHP oceanic eclogites (southwestern Tianshan): implication for a potential deep juxtaposing process during exhumation?. Issue 10 (3rd July 2019) - Tan, Zhou; Gao, Jun; Jiang, Tuo; Wang, Xinshui; Zhang, Xi
ABSTRACT: The Chinese southwestern Tianshan HP–UHP/LT metamorphic complex possesses well-preserved mafic layers, tectonic slices/blocks, boudins/lens of different sizes, and lithology embedded within dominant metavolcanoclastics. A recent study on the ultra-high pressure (UHP) eclogite revealed a short timescale of exhumation (≤10 Ma, 315 ± 5 Ma). However, controversies still exist on some key questions: (1) the reasonable interpretation of spatially close-outcropped high pressure (HP) and UHP slices with respect to regional geodynamics, and (2) if the previous regional scatter Ar–Ar ages proved the existence of internally coherent sub-belts or troubled by dating on samples with notable 40 Ar retention. This study focusses on detailed P – T –time (phengite Ar closure) recovery of samples from a HP eclogite lens and its host rock, the UHP thick-layered eclogite. Based on data from bulk–rock, microprobe analysis, and muscovite Ar–Ar chronological dating, we link phengite growth to potential garnet growth stages via thermodynamic modelling. Facilitated by the P – T –Ar retention% graph, we collect all the regional muscovite Ar–Ar data together with results in this study for evaluating the significance of regional muscovite Ar–Ar ages and set back to geodynamics. According to modelling results, the HP lens eclogite reached peak metamorphism at 550°C, 2.50 GPa with an Ar–Ar muscovite plateau age of 316.9 ± 1.0 Ma that could date the mass phengite growth event during prograde metamorphism. In contrast, the UHP layered eclogite experienced UHP peak burial at 510°C, 2.95 GPa, and then to HP peak metamorphism at 560°C, 2.60 GPa with 311.6 ± 0.7 Ma plateau age that may constrain the cooling age during early exhumation. Noteworthy, both of them share a quite similar early exhumation path despite bearing contrasting prograde metamorphic experiences. With considering updated regional exhumation pattern, this might imply the existence of a potential deep juxtaposing (capture) process between HP slices and exhumating UHP complex, at about 45–60 km depth along subduction plate interface.